Material masterpieces: art collecting and the formulation of French-Jewish identity from Dreyus to Vichy - McAuley, J (2016)
This thesis relies on an extensive series of previously unexploited archival materials in France, Britain, and the United States to examine the role of art collecting among French- Jewish elites after Dreyfus and before Vichy. The families who constituted France's fin-de- siècle Jewish establishment—among others, the Rothschilds and the Reinachs, the Éphrussis and the Foulds, the Camondos and the Cahen d'Anvers—all shared an intense interest in collecting art and material objects. This interest they pursued with passion throughout a period in which the position of French Jews was increasingly uncertain. The Dreyfus Affair had challenged the promise of assimilation and the social station of the "israélite," while economic circumstances and waves of immigration from Eastern Europe had exacerbated extant French anti-Semitism. As plutocrats, many of these elite families were often even the targets of that anti-Semitism, yet they pursued their material interests regardless. Today, the collections they created—mostly of eighteenth-century French art—are their most enduring legacies, either in the form of individual public museums or as additions in other national museums. To that end, this thesis argues that material culture was central to the experiences of these families as Jews and as people in the French fin-de-siècle. The central contention of this thesis is that material culture was a crucial way in which these elites experienced Jewishness in private and especially in public. Beginning with Hannah Arendt (1951) and Michael Marrus (1971), most of the many studies of this fin-de- siècle milieu have tended to consider these individuals in the respective discourses of politics and culture. Few have emphasized their actual lived experiences as people with complex inner lives. Collecting, as archvial materials suggest, was a means of achieving personal sanctuary and solace in the midst of significant personal tragedies as well as an increasingly hostile external environment. It was also a significant means of preserving public dignity. Even fewer studies, after all, have emphasized the way in which French anti-Semitism of the late nineteenth century—from the likes of the journalist Édouard Drumont and the critics Edmond and Jules Goncourt—was often expressed in the language of material culture: Jews were attacked for "inauthentic" aesthetic tastes and for "invading" the realm of French cultural patrimony. As this thesis argues, Jewish elites responded to that material critique in material terms, amassing exhaustive collections of art and objects that, in their eyes, celebrated France and its glorious past. As many of their last wills and testaments suggest, the network of museums they created in the 1920s and 1930s were all subtle arguments for the compatibility of Frenchness and Jewishness. The Holocaust, of course, fundamentally altered the meaning of these museums as well as the memories of those who established them. This dissertation concludes with a reflection on these museums as "lieux de mémoire," material manifestations not only of vanished people but also of a vanished culture.